A simple Schiff base as selective and sensitive fluorescent-colorimetric hydrazine chemosensor. Issue 12 (26th September 2018) - Mondal, Jahangir; Manna, Amit K.; Rout, Kalyani; Singh, Sunil K.; Naskar, Jnan P.; Patra, Goutam K.
ABSTRACT: A new fluorescent-colorimetric chemosensorL has been synthesised by Schiff base condensation reaction between 1, 8-diaminooctane and 4-nitro-benzaldehyde in very good yields. Its photo-luminescent properties and selective detection properties for hydrazine have been examined. The synthesised chemosensor exhibited highly selective fluorescence on-off response for hydrazine amongst a wide range of different metal cations, anions and amines, along with the bare eye colour change from colourless to yellow based on intermolecular hydrogen-bond interaction. The limit of detection of the chemosensorL was estimated as 9.77 × 10 −8  M or 3.12 × 10 −6  g L −1 for hydrazine which is extremely below the limit set by the World Health Organization (WHO) and the binding stoichiometry was proposed to be 1 : 2 based on 1 H NMR spectroscopic techniques and the Job's plot analysis. The proposed sensing mechanism is the hydrogen-bonding interaction which has further been established by Density Functional Theory (Functional Density Theory (DFT)) studies. This recognition feature of sensorL makes it an efficient chemosensor for hydrazine detection in different water samples.